Effects of short-term thermomechanical densification on the structure and properties of wood veneers. Issue 1 (1st January 2017) - Bekhta, Pavlo; Proszyk, Stanisław; Krystofiak, Tomasz; Sedliacik, Jan; Novak, Igor; Mamonova, Miroslava
Abstract: The effects of short-term thermomechanical (STTM) densification temperature and pressure on the changes in surface roughness, wettability, mass loss (ML), thickness and density of alder, beech, birch, and pine wood veneer with low moisture content ( 5%) were investigated. The anatomical structure of veneers was also observed. Veneer sheets were densified using pressure levels of 4, 8 and 12 MPa at three temperatures: 100°C, 150°C and 200°C for 4 min. The results were compared with those of the non-densified veneers. The obtained results show that STTM densification of veneers similarly to long-term densification of solid wood causes irreversible changes in their properties. The STTM-densified veneer surfaces became smoother and more hydrophobic, ML increased slightly while roughness and thickness values decreased significantly, the cell lumens collapsed and a certain amount of fractures in cell walls developed with increasing densification temperature and pressure. All of the investigated wood species showed higher density values after densification. It was found that an even STTM densification of veneers provides stable properties under normal atmosphere conditions; in particular, the thickness and contact angle values were stable for 24 hours after densification, which is an important consideration for industrial applications.